The impact of comprehensive student support on crime - Adam Lavecchia; Philip Oreopoulos; Noah Spencer (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
This study finds substantial reductions to criminal activity from the introduction of a comprehensive high school support program for disadvantaged youth living in the largest public housing project in Toronto. The program, called Pathways to Education, bundles supports such as regular coaching, tutoring, group activities, free public transportation tickets and bursaries for postsecondary education. In this paper, we use a difference-in-differences approach that compares students living in public housing communities where the program was offered to those living in communities where the program was not offered over time. We find that eligibility for Pathways reduces the likelihood of being charged with a crime by 32 percent at its Regent Park location. This effect is driven by a reduction in charges for breaking and entering, theft, mischief, other traffic offenses and Youth Criminal Justice Act offenses.
Keywords: I24; I26; I28; L31; 330; At-risk youth; education and crime; youth programs